Efisiensi Penggunaan Radiasi Matahari dan Respon Tanaman Kedelai (Glycine max L.) terhadap Penggunaan Mulsa Reflektif - Mubarak, Syahrun; ,, Impron; June, dan Tania (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
One of factors affecting the productivity of soybean crop is the availability of solar radiation. Reduction of solar radiation reaching soybean crop by cloud cover especially during rainy season or by shade of trees could potentially decrease soybean production. The availability of radiation for the crop can be increased through the use of reflective mulch to reflect back transmitted radiation to the crop canopy. This study aimed to determine the effect of shade and reflective mulch on crop solar radiation balance and crop productivity responses. A field experiment in Bogor, Indonesia in July 2016 to January 2017, was conducted, applying a Nested Design-two factors model with three replications. The first factor was two levels of shading, i.e., without and with 50% shade; and the second factor was three levels, i.e., without mulch, black silver mulch, and metallic mulch. The results showed that the use of mulch influenced the radiation balance of plants, increasing distribution of radiation reception in plants, solar radiation interception and RUE. The use of mulch caused changes in canopy structure by increase LAI, so that the inhibited radiation was higher. The reflected radiation from the mulch increased production per plants and weight of 1,000 seeds in shaded plants.Keywords: black silver mulch, metallic mulch, radiation balance, radiation interception, shading